Effectiveness of 'Penaga Lilin' (Mesua Ferrea L.) and 'Payung Indonesia' (Hura Crepitans L.) Trees as Thermal Radiation Filters in Outdoor Environment - Shahidan, Mohd Fairuz (2007)
In tropical climates, outdoor open spaces are highly exposed to solar radiation, resulting in uncomfortable conditions for pedestrians and other users. This influences the outdoor energy budget, leading to consequential thermal effects on the overall urban environment and contributing to the urban heat island effect. However, trees and other vegetation can play a significant role in reducing the effects of thermal heat in open spaces by filtering the incoming solar radiation before it reaches the ground. This study compares the effectiveness of two types of tree structural forms in filtering the thermal radiation. The trees are Mesua ferrea L. and Hura crepitans L., representing roundhead trees and horizontal shape species respectively. This study focuses on three variables that influence on solar radiation filtration, namely, transmissivity, leaf area index and shade form. Two evaluation methods were employed in this study; (i) a field measurement programme using a modified net radiometer and other related instruments, and (ii) Ecotect - a computer-based sunshading analysis.Results from this study indicated that both Mesua ferrea L. and Hura crepitans L. contribute significantly to direct thermal radiation modification below their canopies. The average heat filtration under tree canopy for Mesua ferrea L. was found to be 93% with 5% canopy transmissivity, 6.1 of leaf area index, and 35% of shade area. Meanwhile for Hura crepitans L. the average heat filtration under canopy was 79% with canopy transmissivity of 22%, leaf area index of 1.5 and 52% of shade area. Therefore, the study found that Mesua ferrea L. was better in filtering thermal radiation than Hura crepitans L. (93% and 79% respectively). This was attributed to the denser foliage cover and branching habit of Mesua ferrea L. with Leaf Area Index of 6.1 and allowing only 5% transmissivity as compared to Hura crepitans L. foliage density and branching system with Leaf Area Index of 1.5 and allowing for 22% transmissivity. Finally, the study also found that tree canopy characteristics of both species significantly influence thermal radiation filtration.